The Indigenous Contribution to the Lexicon of Nineteenth-Century Honduras According to A. Membreño’s Hondureñismos - Kosteva, Kristina (2024)
Despite of his relevance in Central American lexicography, Alberto Membreño has not received the attention he deserves. Because of that, this paper aims to analyze the collection of Indigenous words in his Hondureñismos (1897), in order to study their importance in this dictionary. Thus, various aspects (such as the number of words that come from Indigenous languages, their etymology, their distribution in lexical fields and their interpretation as americanismo will be examined, so we will be able to understand in a deeper way the contribution of autochthonous languages to Central America’s 19th century lexicography.